2012
DOI: 10.3109/2000656x.2012.730488
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ASCs on the graft survival rates of fat particles in rabbits

Abstract: This study was conducted to explore the effect of adipose-derived stem cells (ASCs) on the graft survival rates of fat particles in rabbits. Six domestic rabbits were used for a 3-month study; 1.4 grams of fat tissues were harvested from the bilateral inguinal regions of each animal. They were cut into granules and divided into three parts (A = 0.4 g, B = 0.4 g, and C = 0.6 g). Part A was centrifuged after 0.075% collagenase digestion for isolation of the stromal vascular fraction (SVF). About 0.2 grams of SVF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…In our past experiments, we observed that excellent results were obtained when fat particles mixed with SVF were grafted. 25 Obviously, similar effects were demonstrated in this experiment. Therefore, we propose that there may be beneficial effects between SVF and fat tissue when transplanting the mixture of both.…”
Section: Graft Survival Ratessupporting
confidence: 87%
“…In our past experiments, we observed that excellent results were obtained when fat particles mixed with SVF were grafted. 25 Obviously, similar effects were demonstrated in this experiment. Therefore, we propose that there may be beneficial effects between SVF and fat tissue when transplanting the mixture of both.…”
Section: Graft Survival Ratessupporting
confidence: 87%
“…Five studies were identified, in which immunocompetent animals were used of which two used rodents (allogeneic cells) [ 16 , 50 ] and the remaining studies used rabbits (autologous cells) [ 17 , 51 , 52 ]. The relative survival improvement for CAL ranged from 1.29- to 4.14-fold compared with their respective control group.…”
Section: Resultsmentioning
confidence: 99%
“…The positive effects of ASC-based approaches in regenerative therapies have been demonstrated in preclinical and clinical studies, for example in cell-assisted lipotransfer or treatment of ischemic diseases [ 9 , 28 , 29 , 30 ]. However, a substantial loss of implanted cells has been documented during the early phase of engraftment [ 12 , 31 ].…”
Section: Discussionmentioning
confidence: 99%